2011
DOI: 10.1287/orsc.1100.0551
|View full text |Cite
|
Sign up to set email alerts
|

Real Options and Investment Mode: Evidence from Corporate Venture Capital and Acquisition

Abstract: Existing research has used real options theory to study corporate venture capital (CVC) investment, yet little work has empirically examined such investment in a comparative setting. In this paper, we begin to address this gap by investigating firms' investment mode choice between CVC and acquisition, which are alternative modes for pursuing external business development and corporate growth. We propose that when exogenous uncertainty elevates the value of real options, firms are more likely to undertake CVC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 82 publications
4
86
0
Order By: Relevance
“…We find an analogous negative interaction effect here due to mutual exclusivity among learning experience and technological uncertainty effects in case of R&D success. In the empirical real options literature, several studies, such as Folta and O'Brien (), Tong and Li (), and others (e.g., Anand, Oriani, & Vassolo, ; Oriani & Sobrero, ; Vassolo et al, ), have examined interactive effects of growth versus deferral options, deferral options interacting with product market competition, interactive effects of different types of uncertainty or the impact of learning/capabilities on firm value. However, these studies are not able to disaggregate or calibrate different value components as we do.…”
Section: Literature and Information Structurementioning
confidence: 99%
“…We find an analogous negative interaction effect here due to mutual exclusivity among learning experience and technological uncertainty effects in case of R&D success. In the empirical real options literature, several studies, such as Folta and O'Brien (), Tong and Li (), and others (e.g., Anand, Oriani, & Vassolo, ; Oriani & Sobrero, ; Vassolo et al, ), have examined interactive effects of growth versus deferral options, deferral options interacting with product market competition, interactive effects of different types of uncertainty or the impact of learning/capabilities on firm value. However, these studies are not able to disaggregate or calibrate different value components as we do.…”
Section: Literature and Information Structurementioning
confidence: 99%
“…Prior work indicates that when firms engage in risky and uncertain interorganizational tie formation, they tend toward minimal commitment and flexible interorganizational arrangements (Folta, 1998;Schildt et al, 2005). This resonates with real-options logic, which has been utilized in several external venturing studies to predict ECV mode engagement (Tong & Li, 2011;van de Vrande et al, 2009). However, our results contrast with this perspective, as we find that firms engaged in exploration-an inherently risky activity-tend to utilize acquisitions more frequently (relative to their overall ECV portfolio) than other firms.…”
Section: Discussionmentioning
confidence: 84%
“…Basu, Phelps, and Kotha (2011) found that firms in technologically intensive industries tend to make more CVC investments than firms in less technologically intensive industries. Similarly, Tong and Li (2011) found that firms are more likely to engage in CVC investments rather than acquisitions when technological uncertainty is high. These previously established direct effect relationships between uncertainty and external venturing mode suggest that technological uncertainty exerts an attenuating influence on the relationship between exploration and the relative usage of acquisitions.…”
Section: The Moderating Role Of Technological Dynamismmentioning
confidence: 92%
“…Several scholars ( [78], [79], [86]) have argued that in the face of high technological and commercial uncertainty, firms are likely to delay their investments in certain technologies. In this case, they make small investments in a certain technological field in order to build familiarity with this new field.…”
Section: Additivity Of Cvc Investmentsmentioning
confidence: 99%